Early prenatal diagnosis of causative homozygous variants in ASCC1 in a fetus with cystic hygroma and additional homozygous variants of unknown significance associated with a neurological phenotype not visible in early gestation: Dual diagnosis or not? - Favier, Maud; Delanne, Julian; Gorincour, Guillaume; Faivre, Laurence; Racine, Caroline; Philippe, Christophe; Duffourd, Yannis; Vitobello, Antonio; Rousseau, Thierry; Martz, Olivia; Tarris, Georges; Oualiken, Camélia; et al. (Prenatal diagnosis, 2024)
A consanguineous couple was referred at 10 weeks of gestation (WG) for prenatal genetic investigations due to isolated cystic hygroma. Prenatal trio exome sequencing identified causative homozygous truncating variants in ASCC1 previously implicated in spinal muscular atrophy with congenital bone fractures. Prenatal manifestations in ASCC1 can usually include hydramnios, fetal hypo‐/akinesia, arthrogryposis, contractures and limb deformities, hydrops fetalis and cystic hygroma. An additional truncating variant was identified in CSPP1 associated with Joubert syndrome. Presentations in CSPP1 include cerebellar and brainstem malformations with vermis hypoplasia and molar tooth sign, difficult to visualize in early gestation. A second pregnancy was marked by the recurrence of isolated increased nuchal translucency at 10 + 2 WG. Sanger prenatal diagnosis targeted on ASCC1 and CSPP1 variants showed the presence of the homozygous familial ASCC1 variant. In this case, prenatal exome sequencing analysis is subject to a partial ASCC1 phenotype and an undetectable CSPP1 phenotype at 10 weeks of gestation. As CSPP1 contribution is unclear or speculative to a potentially later in pregnancy or postnatal phenotype, it is mentioned as a variant of uncertain significance. The detection of pathogenic or likely pathogenic variants involved in severe disorders but without phenotype‐genotype correlation because the pregnancy is in the early stages or due to prenatally undetectable phenotypes, will encourage the clinical community to define future practices in molecular prenatal reporting. Key points What's already known about this topic? Homozygous pathogenic truncating variants in ASCC1 were previously implicated in spinal muscular atrophy with congenital bone fractures. Homozygous pathogenic truncating variants in CSPP1 were previously implicated in Joubert syndrome. What does this study add? This report confirms cystic hygroma as ASCC1 associated fetal presentation. Detection of pathogenic or likely pathogenic variants involved in severe disorders but without phenotype‐genotype correlation because the pregnancy is in the early stages or due to prenatally undetectable phenotypes will encourage the clinical community to define future practices in molecular prenatal reporting.